Conceptual design of a portable electrolyzed water cleaning rig using TRIZ method - Jalil, N. A.; Khalid, Nurul Izzah; Sulaiman, Nurul Shaqirah; Sobri, Shafreeza; Taip, Farah Saleena; Ab. Aziz, Norashikin (Rynnye Lyan Resources, 2021)
The limited budget allocation and storage chemicals space are the main reasons food SMEs manufacturers took cleaning and sanitation for granted. A portable electrolyzed water cleaning rig which can generate sanitation solution and at the same time generated high-speed water will ease the cleaning and sanitation process for SMEs. In this study, the theory of inventive problem solving (TRIZ method) is applied in the development of a portable electrolyzed water cleaning rig. A new conceptual design for the rig, which is robust and affordable is proposed. The rig could improve cleaning efficiency significantly in SME food industry in Malaysia, which is a major cause of a low number of SME with GMP certification. However, the final conceptual design has to undergo several modifications for assembly and manufacturing purposes, which will be performed in further study. The idea of generation for the portable electrolyzed water cleaning rig design was illustrated based on the TRIZ contradiction matrix. This portable rig will be able to generate both strongly acidic electrolyzed water (AcEW) and strongly alkaline electrolyzed water (AlEW) solution continuously. Both cleaning solutions are green cleaning solutions which can replace the commercial cleaning sanitation solutions. The development of the conceptual design of the portable water cleaning rig will help food SMEs tremendously.